Improving Reading Speed and Biology Conceptual Understanding using Speed Reading Method on Students of X-MIA SMA - Edi Sulistiyono; Susriyati Mahanal; Murni Saptasari (Jurnal Pendidikan Sains, 2017)
Abstract: Speed reading method helps students to learn effectively, efficiently, and independently in understanding a reading. This study aims to improve the reading speed and understanding of students’ biology concepts by applying speed reading method. This research was conducted in SMA Bina Bangsa Surabaya in Odd Semester of Academic Year 2015-2016. This research is qualitative research which was done by employing reading speed test and comprehension test of biology concept. The subject of this research was 41 students of X-MIA class in SMA Bina Bangsa Surabaya. The data were analyzed by employing descriptive qualitative. The results showed an increase in average reading speed of 481 wpm, with an average understanding of the concept of 73%.Key Words: speed reading, biology conceptual understanding, reading speedAbstrak: Metode speed reading membantu siswa untuk belajar secara efektif, efisien, dan mandiri dalam memahami suatu bacaan. Penelitian ini bertujuan untuk meningkatkan kecepatan membaca dan pemahaman konsep biologi siswa dengan menerapkan metode speed reading. Penelitian dilakukan di SMA Bina Bangsa Surabaya pada semester ganjil tahun pelajaran 2015-2016. Jenis penelitian ini adalah penelitian kualitatif yang dilakukan dengan uji kecepatan membaca dan uji pemahaman konsep biologi. Subjek penelitian ini adalah 41 siswa kelas X-MIA SMA Bina Bangsa Surabaya. Data tersebut dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan terjadi peningkatan rata-rata kecepatan membaca 481 kpm, dengan rata-rata pemahaman konsep 73%.Kata kunci: speed reading, pemahaman konsep biologi, kecepatan membaca